Implementation Of The Change Of The Chairman Of The Labuhan Batu Selatan Regional People's Representative Council - Zainuddin Zainuddin (International Journal Reglement & Society (IJRS), 2022)
The Provincial Government has a Governor, the Regency Regional Government has a Regent and Regency DPRD, and the City Regional Government has a Mayor and City DPRD. More specifically, Article 18 Paragraph (3) of the 1945 Constitution which states